The Chironomus group (Diptera: Chironomidae) in Lake Winnipeg, Canada - Sæther, Ole A. (Zootaxa, 2012)
Species of the Chironomus group from Lake Winnipeg, Manitoba, Canada are listed and taxonomic and ecological notesgiven. Chironomus (C.) entis Shobanov and C. (C.) bifurcatus dominates the bottom fauna with minor occurrence of fourother larval types. Fourteen species of Chironomus Meigen, one Chaetolabis Townes, and one Lobochironomus Ryser,Wülker et Scholl; one species of Benthalia Lipina, and one Einfeldia Kieffer are present in the light traps. Chironomus(Lobochironomus) sp. and Benthalia brunneipennis (Johannsen) are described on adult male. A key to the Nearctic malesof Einfeldia, Benthalia and Chironomus subgen. Lobochironomus is presented. The significance of the different Chi-ronomus species as indicators of trophic levels is demonstrated by their distribution in Lake Winnipeg. The separation of larval instars is shown approximately to follow Dyar’s rule.